(untitled) (Indian Forester, 1937)
Very little is yet known about the physiology of the individual tree, and still less of the physiology of tree crops. What little information has been obtained nearly all refers to temperate climates, leaving the tropical forests almost unexplored. Only small beginnings have been made in the study of the tropical forest in relation to the soil, to genetic problems and to ecological problems of competition and succession. The study oi trees and crops calls for a special technique both in the collection of data and their analysis. India is in a unique and very favourable position to lead the world in this field, the problems awaiting solution being full of interest to the scientific worker and full of importance on their economic side.